2020
DOI: 10.3390/antibiotics9060286
|View full text |Cite
|
Sign up to set email alerts
|

The Gut of Healthy Infants in the Community as a Reservoir of ESBL and Carbapenemase-Producing Bacteria

Abstract: The recent rapid rise of multi-drug resistant Enterobacteriaceae (MDR-E) is threatening the treatment of common infectious diseases. Infections with such strains lead to increased mortality and morbidity. Using a cross-sectional study, we aimed to estimate the prevalence of gut colonization with extended spectrum beta-lactamase (ESBL) producing Enterobacteriaceae among healthy infants born in Pakistan, a setting with high incidence of MDR-E infections. Stool samples were collected from 104 healthy infants betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
(43 reference statements)
1
14
2
Order By: Relevance
“…In the study by Bunt et al, daycare center attendance has been shown to be a risk factor for preschoolers carrying ESBL/AmpC-producing bacteria. 25 The prevalence of ESBL-EC carriage in the healthy children in the present study was higher than that in France (7.6%) and Spain (31%) 26 , 27 and lower than that in Cambodia (55%) and Pakistan (43%), 28 , 29 which may be partly due to the differences in sanitary conditions, climate, and eating habits in different regions of the world. Although the carriage rate of ESBL-EC in this study was relatively high compared to that observed in the above studies, it was still lower than that in pediatric patients in China, which has been reported to be 46.7%.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In the study by Bunt et al, daycare center attendance has been shown to be a risk factor for preschoolers carrying ESBL/AmpC-producing bacteria. 25 The prevalence of ESBL-EC carriage in the healthy children in the present study was higher than that in France (7.6%) and Spain (31%) 26 , 27 and lower than that in Cambodia (55%) and Pakistan (43%), 28 , 29 which may be partly due to the differences in sanitary conditions, climate, and eating habits in different regions of the world. Although the carriage rate of ESBL-EC in this study was relatively high compared to that observed in the above studies, it was still lower than that in pediatric patients in China, which has been reported to be 46.7%.…”
Section: Discussioncontrasting
confidence: 63%
“… 20 , 32 Although few countries have reported CP-EC carriage among community healthy children to date, a report from Pakistan showed that a quarter of infants in their research harbored CP-EC, indicating that the intestine of healthy children may be a reservoir of CP-EC and should be considered as a serious health issue. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, multidrug resistance (MDR) in E. coli is a major public health issue making E. coli infections more difficult to treat. In addition, as carbapenemase-producing Enterobacterales (CPE) are increasingly detected ( 2 , 3 ) and E. coli is a ubiquitous member of the human gut microbiome, carbapenemase-producing E. coli (CP- Ec ) is also becoming a major actor for the global dissemination of carbapenemase genes ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…By 2050, up to 90% of AMR-related mortality is predicted to occur in countries in Asia and Africa [1], most of which are low-or middle-income. Although systematic investigations are sparse, several studies of healthy children in LMICs [5,7,102] report colonization with enteric multidrug-resistant gram-negative bacteria at rates that far exceed what is observed in the USA and Europe. For example, 82% of 1-2-year-old children in Bangladesh [103] were recently reported to be colonized with third-generation cephalosporin-resistant Enterobacteriaceae, compared to 4.5% of similarly aged children in the USA [104] and~14% in Switzerland [105].…”
Section: Exploring Breastfeeding As a Strategy To Combat Antimicrobiamentioning
confidence: 99%